CircAMOTL1L Suppresses Renal Cell Carcinoma Growth by Modulating the miR-92a-2-5p/KLLN Pathway. (4th October 2021) - Gao, Ling; Shao, Xian; Yue, Qingqing; Wu, Weifei; Yang, Xuejuan; He, Xiaolei; Li, Limin; Hou, Fujun; Zhang, Ruonan
Abstract : Accumulating evidence indicates that the dysregulation of circular RNAs (circRNAs) contributes to tumor progression; however, the regulatory functions of circRNAs in renal cell carcinoma (RCC) remain largely unknown. In this study, the function and underlying mechanism of circAMOTL1L in RCC progression were explored. qRT-PCR showed the downregulation of circAMOTL1L in RCC tissues and cell lines. The decrease in circAMOTL1L expression correlated with the tumor stage, metastasis, and poor prognosis in patients with RCC. Functional experiments revealed that circAMOTL1L inhibited cell proliferation and increased apoptosis in RCC cells. Subcutaneous implantation with circAMOTL1L-overexpressing cells in nude mice decreased the growth ability of the xenograft tumors. Mechanistically, circAMOTL1L served as a sponge for miR-92a-2-5p in upregulating KLLN (killin, p53-regulated DNA replication inhibitor) expression validated by bioinformatics analysis, oligo pull-down, and luciferase assays. Further, reinforcing the circAMOTL1L–miR-92a-2-5p–KLLN axis greatly reduced the growth of RCC in vivo . Conclusively, our findings demonstrate that circAMOTL1L has an antioncogenic role in RCC growth by modulating the miR-92a-2-5p–KLLN pathway. Thus, targeting the novel circAMOTL1L–miR-92a-2-5p–KLLN regulatory axis might provide a therapeutic strategy for RCC.